VD_FINDINFO Décision / 2011 / 650 vom 3. November 2011 - VD Tribunal cantonal (2011)
DISJONCTION DE CAUSES, PRINCIPE DE LA CÉLÉRITÉ, CONNEXITÉ MATÉRIELLE | 29 CPP (CH), 30 CPP (CH), 329 al. 2 CPP (CH), 329 CPP (CH)